Effect of Agrochemicals Based on Vegetable and Mineral Oil on the Viability of Entomopathogenic Fungi Beauveria bassiana (Bals.) Vuillemin, Metarhizium anisopliae (Metsch.) Sorokin and Paecilomyces sp. Bainier - da Silva, Roberta; Neves, Pedro; Santoro, Patrícia; Cavaguchi, Silvia (BioAssay, 2009)
Many phytosanitary products have either vegetable or mineral oils as active ingredients or adjuvants. However, there are few papers that investigated the effects of these products on entomopathogenic fungi. Most studies refer to the use of oils as adjuvants in entomopathogen formulations with entomopathogens, and not as adjuvants in the tank mix. The objective of this study was to verify the compatibility of the entomopathogenic fungi Beauveria bassiana (Bals.) Vuillemin, Metarhizium anisopliae (Metsch.) Sorokin, and Paecilomyces sp. Bainier with agrochemicals based on mineral and vegetable oil in the tank mixes. Fourteen products were tested at their average recommended field rates. Conidial viability was estimated based on the percentage of germinated conidia and the number of colony-forming units (CFU). The commercial pesticides Assist, Attach, Agnique CSO 40-B, Agnique ESO 81-B Dytrol, Iharol, Joint Oil, Max Óleo, Natur Óleo, Nimbus and Veget Oil did not affect germination of the B. bassiana isolate CG 432. Attach, Agnique CSO 40-B, Dash, Dytrol, Agnique ESO 81-B, Natur Óleo and Veget Oil were compatible with M. anisopliae isolate UEL 50 and OPPA, Nimbus and Assist was compatible to Paecilomyces sp. isolate UNI 31. Therefore, the selected oils can be used in tank mixes with conidia of tested entomopathogenic fungi without any risk of detrimental effects.